2017
DOI: 10.1039/c7cp01606a
|View full text |Cite
|
Sign up to set email alerts
|

Defect-promoted photo-electrochemical performance enhancement of orange-luminescent ZnO nanorod-arrays

Abstract: Intentionally defect-rich zinc oxide (ZnO) nanorod-arrays were grown from solution by carefully adjusting the concentration ratio of the growth-precursors used followed by various post-deposition thermal treatments. Post-deposition rapid thermal annealing (RTA) at moderate temperatures (350 °C-550 °C) and in various atmospheres was applied to vary the defect composition of the grown nanorod-arrays. It is demonstrated that, intense, defect-related orange emission occurs solely upon RTA around 450 °C and is esse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 61 publications
3
40
0
Order By: Relevance
“…38 In that paper evidences have been presented that the oxygen vacancy-zinc interstitial defect complex V O -Zn i might be responsible for the observed orange emission. Due to advances in computational studies of ZnO over the past decades, it is now widely accepted that the deep-level oxygen vacancy is thermodynamically stable in its neutral V O and doubly ionized state V O ++ with V O being more abundant due to the lower formation energy.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…38 In that paper evidences have been presented that the oxygen vacancy-zinc interstitial defect complex V O -Zn i might be responsible for the observed orange emission. Due to advances in computational studies of ZnO over the past decades, it is now widely accepted that the deep-level oxygen vacancy is thermodynamically stable in its neutral V O and doubly ionized state V O ++ with V O being more abundant due to the lower formation energy.…”
Section: Resultsmentioning
confidence: 99%
“…38 It is noteworthy that samples prepared on ALD deposited seed layers showed generally less orange emission when compared to nanorodarrays grown on spin-coated seed layers. When co-annealing nanorodarrays prepared on different seed layers and different substrates (glass, gallium nitride, FTO, sapphire) it was found that the substrate does not influence the orange emission.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations